Study of Essential Oil from Malaysian Curry Leaves - Nur Aminatulmimi, Ismail; Jamil, Roslan; Hafizah, Ramli; Sharifah Fathiyah, Sy Mohamad (2014)
Essential oils of Murraya koengii or commonly known as curry leaves’ obtained from curry trees grown in the local area of Malaysia was studied. Conventional hydro distillation process was used to extract the oil from the leaves. The highest yield from the extraction is to be at 0.22% for 9 hours of extraction time. The analysis was performed using GC-MS which detects the presence of 30 different components, majorly hydrocarbons. The result shows the existing of alpha-pinene and beta-myrcene that provides insight to the potential of using the oil as active ingredients for natural based insect repellent.